Elaboration on Specialization in Crime: Disaggregating Age Cohort Effects. (September 2013) - Yonai, Shachar; Levine, Stephen Z.; Glicksohn, Joseph
To elaborate past research, this study examines the course of specialization and versatility with maturation and contends that specialization develops in a nonrandom manner, as suggested by the orthogenic principle of human development. To examine the development of specialization and versatility, forward specialization coefficients were disaggregated for three age cohorts over a 20-year follow-up period in a sample of high-risk youth ( n = 3, 652) with 54, 175 arrests. Results show that forward specialization coefficients were generally of moderate magnitude and, across age cohorts, developed modestly in an age-graded manner for the youngest cohort. In conclusion, the results provide preliminary support for the orthogenic theory among early first-admission youth.